Device-free localisation in the context of domestic energy saving control methods - Naghiyev, Eldar (2014)
A reduction in greenhouse gas emissions by the energy sector is required to decelerate global warming. With the domestic sector being the biggest energy consumer, a great amount of saving potential is available in the operation of dwellings.